Building human capital for the tourism sector : a case study from Yemen - Al-Saqqaf, Raidan Abdulaziz (2018)
This thesis examines how investing in tourism education was explored as an attractive national development policy in Yemen, where this education would provide the human capital needed for the sector to grow. This examination adopted a dual lens, namely the lens of policy makers responsible for the creation of this educational process as well as that of the students involved. The underlying thought for this research can be summed up in the simple notion: How successful is an educational institution in creating human capital for the tourism sector as seen by both the policymakers and the young people engaged? Responding to this question requires considering the intended goals of both policymakers and students, seen as to accelerate national development and individual wellbeing respectively. Investigating this question is important, particularly given Yemen’s developmental status as a Least Developed Country (LDC) experiencing recurrent cycles of instability, and based on the human capital premise that investing in education contributes positively to achieving development outcomes across the board.